Effectiveness of drotaverine hydrochloride in progression of labour - Thapa, Meena; Saha, Rachana; Pradhan, Amita; Shrestha, Sweety (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: This study was done to compare the effectiveness of drotaverine hydrochloride and valethamate bromide in shortening duration of labour. Methods: It is a hospital based prospective study, carried out in the department of Obstetrics & Gynaecology at Kathmandu Medical College Teaching Hospital (KMCTH), Sinamangal from 1st June to 31st August 2005. 99 patients, who were in active labour, were taken into the study. Out of which 50 were in drotaverine group (Group 1) who had received 40 mg of drotaverine hydrochloride intramuscularly at 3 to 5 cm dilatation of the cervix. Rest of 49 patients were in valethamate bromide group (Group 2). They received 3 doses of 8 mg valethamate bromide and 20 mg hyoscin butyl bromide intravenously half an hour interval. Result: The injection-delivery interval was studied in both Groups. The duration of injection-delivery interval was found to be almost equal in primigravidae of both Groups (p=0.72). But in multigravidae interval was significantly shorter in drotaverine Group (p=0.03). Conclusion: Both drotaverine and valethamate bromide are equally effective in shortening duration labour in primigravidae, where as drotaverine is more effective in multigravidae in accelerating labour. Keywords: Drotaverine, Valethamate bromide, cervical dilatation, labour acceleration doi:10.3126/njog.v2i2.1447 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 9 - 11